Recurrence of pulmonary tuberculosis in India: Findings from the 2019-2021 nationwide community-based TB prevalence survey. - Prathiksha Giridharan; Sriram Selvaraju; Raghuram Rao; Kiran Rade; Kannan Thiruvengadam; Smita Asthana; Rakesh Balachandar; Sampada Dipak Bangar; Avi Kumar Bansal; Jyothi Bhat; Debjit Chakraborty; Vishal Chopra; et al. (PLoS ONE)
Recurrent Tuberculosis patients contribute to a significant proportion of TB burden in India. A nationwide survey was conducted during 2019-2021 across India among adults to estimate the prevalence of TB. A total of 322480 individuals were screened and 1402 were having TB. Of this, 381 (27.1%) had recurrent TB. The crude prevalence (95% CI) of recurrent TB was 118 (107-131) per 100,000 population. The median duration between episodes of TB was 24 months. The proportion of drug resistant TB was 11.3% and 3.6% in the recurrent group and new TB patients respectively. Higher prevalence of recurrent TB was observed in elderly, males, malnourished, known diabetics, smokers, and alcohol users. (p<0.001). To prevent TB recurrence, all treated tuberculosis patients must be followed at least for 24 months, with screening for Chest X-ray, liquid culture every 6 months, smoking cessation, alcohol cessation, nutritional interventions and good diabetic management.